Implications of the Implementation of the ISO 9001:2015 Quality Management System on Employee Performance and Organizational Culture in Senior High Schools - Sudargini, Yuli (Journal of Industrial Engineering & Management Research, 2019)
This study aims to determine the effect of implementing the ISO 9001:2015 quality management system on employee performance and organizational culture with the object of Senior High School. This study used a questionnaire method as the main data collection tool which was distributed to as many as 210 respondent teachers who were selected by simple random sampling. Data analysis using structural equation modeling (SEM) with data processing tools SmartPLS 3.0 program. The results of this study indicate that there is a significant effect of the ISO 9001 quality management system on organizational culture and teacher performance is positively and significantly influenced by the ISO 9001:2015 quality management system.